2008
DOI: 10.1063/1.2900647
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic couplings from time-dependent density functional theory. II. Successes and challenges of the pseudopotential approximation

Abstract: We present extensive calculations of nonadiabatic couplings (NACs) between the electronically ground and excited states of molecules, using time-dependent density functional theory (TDDFT) within (modified) linear response [C. Hu et al. J. Chem. Phys. 127, 064103 (2007)]. Our approach is implemented in the pseudopotential framework, with the consideration of nonlinear core corrections. The features of either the ordinary Jahn-Teller conical intersections in X(3) (X=Li, Na, K, Cu, Ag, Au) trimers, or the ellipt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 62 publications
2
32
0
Order By: Relevance
“…The Casida-ansatz forces are also different from the ND values, and the differences become smaller when approaching the zero point, which is the same for all cases. In an analogous way, the accuracy problem for the first-order NAC is also reported by Hu et al [37]. They found that the sum rule for NAC vectors [42] from the h-matrix formulations is not satisfied when nonhydrogen atoms are involved.…”
Section: E Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The Casida-ansatz forces are also different from the ND values, and the differences become smaller when approaching the zero point, which is the same for all cases. In an analogous way, the accuracy problem for the first-order NAC is also reported by Hu et al [37]. They found that the sum rule for NAC vectors [42] from the h-matrix formulations is not satisfied when nonhydrogen atoms are involved.…”
Section: E Discussionsupporting
confidence: 56%
“…Extrapolation of the APES indicates that the Renner-Teller glancing intersection point is located at the linear geometry [corresponding to y = 0 in Fig. 3(a)], as shown in a previous study [37]. Figure 3(c) represents the calculated y-direction forces on the Si atom.…”
Section: Forces For the Sih + 2 Moleculesupporting
confidence: 57%
“…This equation was derived by Casida [54] and then applied by Tavernelli et al [14,156,157] and Hu et al [214,215] for the calculation of the NAC vectors between the ground state and an excited state. A similar equation was also given in ref.…”
Section: The Matrix Elements In Lr-tddftmentioning
confidence: 99%
“…30 Since the publication of Ref. 28, several competing methods have been developed along similar lines, [31][32][33][34][35][36][37][38][39][40] only some of which have employed an atom-centered basis. The Gaussian-basis implementation of the method of Hu et al includes Pulay terms associated with the one-electron integrals.…”
Section: A Derivative Couplingsmentioning
confidence: 99%